MASP-1 and MASP-2 Serum Levels Are Associated With Worse Prognostic in Cervical Cancer Progression - Maestri, Carlos Afonso; Nisihara, Renato; Mendes, Hellen Weinschutz; Jensenius, Jens; Thiel, Stephen; Messias-Reason, Iara; de Carvalho, Newton Sérgio (Frontiers in Immunology, 2018)
Background: MBL-associated serine proteases (MASP-1, MASP-2, MASP-3, MAp-44, and MAp-19) are key factors in the activation of the lectin pathway of complement. Serum levels of these components have been associated with recurrence and poor survival of some types of cancer, such as colorectal and ovarian cancer. In this investigation, we determined the serum levels of MASP-1, MASP-2, MASP-3, MAp-44, and MAp-19 in patients with cervical cancer and cervical intraepithelial neoplasia (CIN). Methods:A total of 351 women who underwent screening for cervical cancer or treatment at the Erasto Gaertner Cancer Hospital in Curitiba-Brazil, were enrolled in the study. Based on their latest cervical colposcopy-guided biopsy results, they were divided into four groups: CIN-I: n = 52; CIN-II: n = 73; CIN-III: n = 141; and invasive cancer: n = 78. All the serum protein levels were determined by time-resolved immunofluorometric assay (TRIFMA). Results:Patients with invasive cancer presented significantly higher MASP-2, MASP-1, and MAp-19 serum levels than other groups (p < 0.0001; p = 0.012; p = 0.025 respectively). No statistically significant differences in MASP-3 and MAp-44 serum levels were found between the four studied groups. In addition, high MASP-2, MASP-1, and MAp-19 serum levels were significantly associated with poor survival in patients with invasive cancer and relapse (p = 0.002, p = 0.0035 and p = 0.025, respectively). Conclusion:High MASP-2, MASP-1, and MAp-19 serum levels were associated with cervical cancer progression and worse disease prognosis. These novel findings demonstrate the involvement of the serine proteases of the lectin pathway in the pathogenesis of cervical cancer and future investigations should clarify their role in the disease process.